The princess and the P.I. - Payne, Nikki, 1982- (Berkley Romance, 2025)
"An amateur online sleuth must enlist the help of a jaded PI to clear her name while taking down a shady tech start-up in this exhilarating romantic caper. Famed Reddit detective Fiona Addai is great at solving problems -- online, that is. Cold cases, reality TV scandals, everyone calls on @Princess_PI. It's her way of escaping her strict religious life at home and the memory of her brilliant brother's sudden death. But when the sheltered sleuth tries to apply her inquisitive skills to real life, her plan to reclaim her late brother's invention from the ruthless corporation that stole it goes disastrously wrong. Now, instead of getting justice, Fiona finds herself accused of murder. Maurice Bennett is no stranger to insomnia. These days, he's not losing sleep over the cases he's solving -- but running from the one he couldn't. Instead, he's been settling for small-time scandals that don't stir up the guilt he's buried. But when he spots Fiona Addai at the center of a murder investigation, something clicks. And for the first time in a long while, Maurice feels that old spark of intrigue. However, Fiona is not the helpless damsel she appears to be. Sure, she needs Maurice's help to clear her name, but she's got conditions of her own: she wants a crash course in real-world detective work. Maurice isn't exactly thrilled. With every late-night stakeout and tension-filled interrogation, their partnership starts to feel a little too close for comfort. To bring the real killer to light, they'll need to trust each other and that might be the most dangerous gamble of all." --